The analysis of research on internet marketing - Davidavičienė, Vida; Sabaityte, Jolanta (Business: Theory and Practice, 2014)
The targeted development of internet marketing faces the dynamic environment and its alterations that occur both – in business terms and conditions and in the use of etools and applicable concepts. The growing importance of internet marketing is indicated by a growth in emarkets, an increasing number of new generation consumers, investments of organizations in ebased decisions, a strong interest of scientists representing different fields as well as by widening the base of knowledge related to the above introduced phenomenon. Despite a continuously increasing amount of scientific literature on Internet marketing, this area of research is still at the initial stage. The article is aimed at analysing the fields of ongoing researches into Internet marketing and at identifying the areas required for deeper examination. The article has applied for the methods such as a comparative analysis and summary of scientific literature, information comparison and techniques for grouping and the graphical visualization of information.Tyrimų internetinės rinkodaros srityje analizėSantraukaVykdant kryptingą internetinės rinkodaros plėtrą, susiduriama su kintančia aplinka. Vyksta tiek verslo sąlygų, tiek naudojamų e. priemonių bei taikomų koncepcijų pokyčiai. Internetinės rinkodaros svarbos augimas pasireiškia augančiomis e. rinkomis, didėjančiu naujos kartos vartotojų skaičiumi, organizacijų investicijomis į e. sprendimus, mokslininkų iš įvairių sričių susidomėjimu ir su šiuo reiškiniu susijusios žinių bazės plėtote. Nepaisant gausių mokslinių tyrimų internetinės rinkodaros tema, ši tyrimų sritis gali būti įvardijama kaip sparčiai besivystanti. Šio straipsnio tikslas – išanalizuoti vykdomus internetinės rinkodaros tyrimus ir identifikuoti gilesnių tyrimų reikalaujančias sritis. Straipsnyje taikyti tyrimo metodai yra mokslinės literatūros analizė ir apibendrinimas, analizei naudoti informacijos lyginimo, grupavimo ir grafinio informacijos vaizdavimo metodai.Reikšminiai  žodžiai:  internetinė  rinkodara,  internetinės  rinkodaros  aplinka,  komunikacija,  internetinės  rinkodaros  tyrimų  sritys.